Europeanization of administrative law in Ukraine: theoretical and methodological foundations - Юринець, Юлія Леонідівна (Scientific works of Kyiv Aviation Institute. Series Law Journal "Air and Space Law", 2015)
Consider the need for and characteristics of the process of Europeanisation of administrative law of Ukraine as a European-style development of legal thinking and practice of the European law-making and enforcement activities of the public administration. It is proved that in this direction Ukraine has not passed the proper way, that is connected with the strong influence of the negative legacy of the post-Soviet administration. It is shown that the Europeanization of Ukrainian law related to both the assimilation of the achievements of the European Union and the Council of Europe achievements in their interaction and mutual influence It is proved that the concept of «Europeanization» of administrative law (as the law in general) is much broader than adapting, because Europeanization involves not limited to the formal inclusion of the law "European-style" (although this is also important) in the national legislation of Ukraine and persistent implementation of European style legal thought and European practice of law-making and enforcement of public administration, construction, distribution and institutionalization of formal and informal practices, rules, procedures and standards that are recognized and implemented in the processes of public administration of the European Union and the Council of Europe, given the role of social self-organization and influence return links to management decisions. Denies the concept of Europeanization without European integration, because it is aimed at preservation of post-Soviet state of public administration and administrative law in Ukraine.